Fluorescence Enhancement of a Metal‐Organic Framework for Ultra‐Efficient Detection of Trace Benzene Vapor - Li, Wen‐Bin; Wu, Ying; Zhong, Xiao‐Feng; Chen, Xiong‐Hai; Liang, Gang; Ye, Jia‐Wen; Mo, Zong‐Wen; Chen, Xiao‐Ming (Angewandte Chemie International Edition, 2023)
Indoor detection of volatile organic compounds (VOCs) concentration is necessary due to the serious toxicity hazards even at trace level. However, physisorbents usually exhibit weak interactions especially in the presence of trace concentrations of VOCs, thus exhibiting poor responsive signal. Herein, we report a new flexible metal–organic framework (MOF) that exhibits interesting pore‐opening behavior after immersing in H2O. The pore‐opening phase shows significant (≈116 folds) and extremely fast (<1 minute) fluorescence enhancement after being exposed to saturated benzene vapor. The limit of detection concentration for benzene vapor can be calculated as 0.133 mg L−1. Thus this material represents the first MOF to achieve visual detection of trace benzene vapor by the naked eyes. Theoretical calculations and single‐crystal structure reveal that the special “bilateral π–π stacking” interactions between the host and guest, which facilitate electron transfer and greatly enhance the intensity of fluorescence. A new flexible metal–organic framework (MOF) exhibits significant and sensitive fluorescence “turn‐on” behavior for benzene vapor by virtue of unique “bilateral π–π stacking” interactions, enabling visual detection of a trace level of benzene for the first time.